A Patient with Severe Fever with Thrombocytopenia Syndrome (SFTS) Infected from a Sick Dog with SFTS Virus Infection - Oshima, Hiroaki; Okumura, Hironobu; Maeda, Ken; Ishijima, Keita; Yoshikawa, Tomoki; Kurosu, Takeshi; Fukushi, Shuetsu; Shimojima, Masayuki; Saijo, Masayuki (Japanese Journal of Infectious Diseases, 2022)
Severe fever with thrombocytopenia syndrome (SFTS) caused by Dabie bandavirus (formerly SFTS virus, SFTSV), which belongs to the Bandavirus genus (formerly Phlebovirus genus) of the Phenuiviridae family (formerly Bunyaviridae family), is a tick-borne novel bunyavirus infection with high rates of mortality. SFTSV infection was diagnosed virologically in a 4-year-old dog with symptoms of lethargy and anorexia in western Japan in June 2017. The dog’s owner, a man in his 40s, had taken care of the sick dog and became sick 10 days after disease onset in the dog, showing symptoms, such as fever, arthralgia, headache, nausea, and vomiting. Total blood cell counts revealed leukocytopenia and thrombocytopenia. He was treated as an outpatient. He had no scars suggesting that he had not been bitten by ticks. He was diagnosed as having SFTS via the detection of IgM and neutralizing antibodies to SFTSV. The patient was directly infected with SFTSV from the SFTSV-infected dog. In conclusion, humans can be at a risk of SFTSV infection through direct contact with sick dogs infected with SFTSV.